ACOMPANHAMENTO DE ADOLESCENTES EM USO DE DIU EM DOURADOS – MATO GROSSO DO SUL - Henrique Campos Neves , Paulo; Rolim Baracho , Eduarda; Maria Ribera Lopes Spessoto, Márcia; Faria Gonçalves, Mariana; Luiza Araújo Gomes, Pamela; Avila Silva, Poliana (ANAIS DO ENIC, 2026)
-